SENSITIVITY TEST OF STREPTOCOCCUS SPP. ISOLATED FROM PORCINE RESPIRATORY DISEASE COMPLEX AGAINST KANAMYCIN, STREPTOMYCIN AND DOXYCYCLINE - Purba, Dwi Arso; Gelgel, Ketut Tono Pasek; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana, 2022)
Respiratory diseases in pigs often occur in the production of modern pigs around the world and known as Porcine Respiratory Disease Complex (PRDC). Prevention of PRDC can only be done if the infecting agent is bacteria. The bacteria that are most often isolated in complex pig duct disease are Streptococcus spp. This study was conducted to determine the sensitivity pattern of Streptococcus spp. isolated from animals with PRDC symptoms on kanamycin, streptomycin and doxycycline. Isolates were taken from the results of the PRDC case study of pig origin in Tabanan, Gianyar and Badung regencies. Pure isolates were then planted in blood agar and a sensitivity test was carried out using the Kirby-Bauer method for each antibiotic. Bacteria can be resistant, intermediate and sensitive to antibiotics tested. This gives rise to a pattern of sensitivity to antibiotics so that resistant germs will cause treatment failure. The results showed that hemolytic ? Streptococcus isolates were 60% sensitive to kanamycin, 100% sensitive to streptomycin, 40% resistant to kanamycin and 100% resistant to doxycycline. While hemolytic ? Streptococcus isolates were 100% sensitive to kanamycin and streptomycin but 100% were resistant to doxycycline.